An Analysis of The Agribusiness Communication Structure of Dairy Cattle Farmers: The Case Study of The Tegal Mandiri Farmer Group - Gandasari, Dyah; Sugiarto, Mochamad; Dwidienawati, Diena (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
Problems in dairy cattle agribusiness require attention not only from the farmers themselves but also from farmer organizations. To understand the communication patterns among group members in the agribusiness sector, including the exchange of information related to cattle production, animal health, and wholesale prices, it is essential to analyze the communication network of the dairy cattle farmer group. This network is significant because it serves as the hub of organizational communication, both internally and externally. This research seeks to analyze the communication structure of the dairy cattle farmer group and investigate the relationship between the respondent characteristics and the communication networks within the Tegal Mandiri farmer group in Bogor Regency. The Social Network Analysis (SNA) method and a quantitative approach were used to conduct the research, with the Tegal Mandiri farmer group members in Bogor Regency as the unit of analysis. The group communication structure was analyzed using degree and closeness centrality, and the relationship between respondent characteristics and the communication network was analyzed using Spearman rank correlation. IBM SPSS Statistics 26 and UCINET 6 were the tools used for analysis. The study revealed that 1) the average degree centrality of the group was between 1.00 and 2.20, and the average closeness centrality was between 400.00 and 558.10. 2) The respondents' characteristics of farmers were significantly related to the communication networks within the group. The study found that the communication structure of the Tegal Mandiri farmer group exhibited low connectivity and an ineffective coordination forum.